The bacterial pangenome as a new tool for analysing pathogenic bacteria. (September 2015) - Rouli, L.; Merhej, V.; Fournier, P.-E.; Raoult, D.
Abstract: The bacterial pangenome was introduced in 2005 and, in recent years, has been the subject of many studies. Thanks to progress in next-generation sequencing methods, the pangenome can be divided into two parts, the core (common to the studied strains) and the accessory genome, offering a large panel of uses. In this review, we have presented the analysis methods, the pangenome composition and its application as a study of lifestyle. We have also shown that the pangenome may be used as a new tool for redefining the pathogenic species. We applied this to the Escherichia coli and Shigella species, which have been a subject of controversy regarding their taxonomic and pathogenic position. Highlights: Pangenome is a new way of studying pathogenic bacteria. Pangenome can be used as a taxonomic tool. This review describes pangenome in the world of pathogenic bacteria.